2014
DOI: 10.1089/lap.2013.0429
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Metachronous Hernia Following Negative Laparoscopic Evaluation for Contralateral Patent Processus Vaginalis: A Meta-analysis

Abstract: CMIH following negative laparoscopic evaluation for CPPV was a rare but possible phenomenon. Choosing the transumbilical approach, transinguinal laparoscopy with a large angle, low-pressure pneumoperitoneum, and broad CPPV definition would probably reduce the occurrence of such CMIHs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The PRISMA flow diagram is illustrated in Fig 1 and excluded studies and reasoning for exclusion are listed in Table 2 below [15–60]. …”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram is illustrated in Fig 1 and excluded studies and reasoning for exclusion are listed in Table 2 below [15–60]. …”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, to date, reports on adults have seldom discussed the risk factors for CIH repair. Unlike infants and children, the risk factors associated with and results of CIH repair have been widely discussed [ 4 , 5 ]. Only one study used a non-Medicare claims database to analyze the risk factors for treatment of CIH and showed that an older age and prostate disease were risk factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore laparoscopy is a sensitive method with which to detect CPPV and a good way to prevent MIH at the expense of an overtreatment of CPPV, but it is not a precise way to predict CIH. Importantly negative evaluation of CPPV does not exclude the possibility of CIH ( 13 ).…”
Section: Discussionmentioning
confidence: 99%